Study on Antiweathering Support Technology of Thin Spray-On Liners in Shallowly Buried Coal Seam Roadway under Corrosion Condition. (24th May 2022) - Zhang, Jie; Zhuo, Qing-Song; Yang, Sen; Yang, Tao; Wang, Bin; Bai, Wen-Yong; Wu, Jian-Jun; He, Yi-Feng; Li, Hong-Ru
Abstract : The thin spray-on liner is an inorganic polymer product that has been widely used to support mine perimeter rock roadways, but it is mainly used in metallic hard rock roadways with high rock strength and is less used in roadways affected by roadway corrosion and weathering in shallowly buried coal seams. Therefore, this study studies the thin spray-on liner support technology under such geological conditions. First, the causes of anchor support failure in this condition are analyzed, and it is concluded that alkaline ionized water corrodes the anchor rods, and chloride ions in the water play a role in accelerating the degree of anchor rod corrosion. Next, microscopic testing was used to determine the content of weathering and swelling minerals contained in the roof rock and the development of tectonic fissures. Third, the loosening circle of the surrounding rock is theoretically calculated and used as a basis to design the anchor mesh rope support parameters for the roadway. Finally, the construction process of a thin spray-on liner anticorrosion and antiweathering support technology is introduced. This technology improves the anchor force environment of anchor rods while incorporating anchor rods (ropes)—rock—metal mesh into the support system to play a coupling support role. On-site monitoring is performed to derive the optimum thickness of the spraying layer in different environments. At the same time, the deformation of the roadway surrounding rock and the anchor force can be improved to meet the requirements of anticorrosion and antiweathering and tighten the roadway surrounding rock. Compared with concrete support technology, the economic and environmental benefits of this support technology are apparent, and it helps to promote the application in shallowly buried coal seam mines.